THE INFLUENCE OF TECHNOLOGICAL FACTORS ON THE FORMATION OF THE FILLED POLYMER MATRIX OF PLASTOCONCRETE - Biloshitska, N. I. (Science and Transport Progress, 2009)
In the article the research results of influence of technological factors on properties and characteristics of the plastoconcretes under development for repair-reconstruction work are presented.